2020
DOI: 10.1016/s2213-2600(20)30183-1
|View full text |Cite
|
Sign up to set email alerts
|

Screening and triage at health-care facilities in Timor-Leste during the COVID-19 pandemic

Abstract: Elsevier has created a COVID-19 resource centre with free information in English and Mandarin on the novel coronavirus COVID-19. The COVID-19 resource centre is hosted on Elsevier Connect, the company's public news and information website.Elsevier hereby grants permission to make all its COVID-19-related research that is available on the COVID-19 resource centre -including this research content -immediately available in PubMed Central and other publicly funded repositories, such as the WHO COVID database with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Further, this study shows that the dengue cases reported by each municipality in Timor-Leste had a significant association with the presented COVID-19 cumulative case number. However, in consideration of this result, we assumed the existence of an uncertain diagnosis among these two disorders due to Timor-Leste's fragile healthcare system ( 48 ), particularly a lack of clinical laboratory systems. Furthermore, the coronavirus disease 2019 (COVID-19) has non-specific clinical and laboratory characteristics ( 49 ), which might be similar to other viral infections, including dengue.…”
Section: Discussionmentioning
confidence: 99%
“…Further, this study shows that the dengue cases reported by each municipality in Timor-Leste had a significant association with the presented COVID-19 cumulative case number. However, in consideration of this result, we assumed the existence of an uncertain diagnosis among these two disorders due to Timor-Leste's fragile healthcare system ( 48 ), particularly a lack of clinical laboratory systems. Furthermore, the coronavirus disease 2019 (COVID-19) has non-specific clinical and laboratory characteristics ( 49 ), which might be similar to other viral infections, including dengue.…”
Section: Discussionmentioning
confidence: 99%
“…Of the tools proposed for use in LMICs, 51–31 for screening, 5 for triage, and 15 for severity scoring were deemed feasible in LRS. The most notable of these was the integrated screening and triage process used by Howitt et al 28 in Timor-Leste. The algorithm was adapted from Ayebare et al 29 (Uganda) with the removal of laboratory testing for COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…A plan was made for patients to be given structured appointment times, and only one patient to be in the facility at a pre‐set time. A pre‐designed standardised questionnaire screening for COVID‐19 symptoms was utilised 9 . ETHF had regularly shipped containers of personal protective equipment and hand sanitiser to Timor‐Leste throughout the pandemic, enabling their availability at the clinic.…”
Section: Methodsmentioning
confidence: 99%
“…A pre-designed standardised questionnaire screening for COVID-19 symptoms was utilised. 9 ETHF had regularly shipped containers of personal protective equipment and hand sanitiser to Timor-Leste throughout the pandemic, enabling their availability at the clinic.…”
Section: Clinic Designmentioning
confidence: 99%